The sexual contract - Pateman, Carole (Standford University Press, 1988)
In this remarkably original work of political philosophy, one of today's foremost feminist theorist challenges the way contemporary society functions by questioning the standard interpretation of an idea that is deeply embedded in American and British political thought: that our rights and freedoms derive from the social contract explicated by Locke, Hobbes, and Rousseau and interpreted in the United States by the Founding Fathers.
Keywords: 1900-1999; 1980-1989; amériques; citoyenneté; contrat social; cours; discipline; droits des femmes*; fem1000; incontournable; philosophie politique; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques; théories féministes; états-unis

Can the Subaltern Speak? - Spivak, Gayatri Chakravorty (Marxism and the Interpretation of Culture, 1988)
Keywords: 1900-1999; 1980-1989; approches et analyses; cours; fem1000; histoire et politique; incontournable; inégalités; mondialisation; pol4022; premier cycle; périodes historiques; systèmes d'oppressions; thématiques; théories féministes; études postcoloniales

La contrainte à l'hétérosexualité et l'existence lesbienne - Rich, Adrienne (Nouvelles Questions Féministes, 1981)
Cette article rejette la vision de l'existence lesbienne comme marginale et déviante et, renversant la question, insiste sur la nécessité de se demander ce qui pousse les femmes dans les normes hétérosexuelles, et comment l'institution politique de l'hétérosexualié féminine est maintenue. Pour l'auteur, le refus de considérer cette question, ou le fait de la négliger, bloquent actuellement la théorie féministe. La destruction sociale de l'identification première des femmes avec les femmes est la clef du maintien de la suprématie masculine. Ce fait doit être courageusement reconnu et analysé par les nonlesbiennes aussi bien que par les lesbiennes féministes si nous voulons briser le droit que s'arrogent les hommes à l'accès sexuel aux femmes et l'institution qui les soutient. This paper rejects the treatment of lesbian existence as marginal or deviant, suggesting that we ask, rather, what impels women into heterosexual patterns, and how the political institution of female heterosexuality is maintained. I see the avoidance or negleet of this question as a stumbling-block for feminist theory at present. The forcing-underground and erasure of women's primary identification with women is a key to the maintenance of male supremacism. It must be courageously recognized and analyzed by non-lesbian as well as by lesbian feminists if we are to break the presumptive right of male sexual access to women and the institutions which support this.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; cycles supérieurs; fem1000; fem7000; incontournable; lesbianisme; lit3220; pol4212; premier cycle; périodes historiques; ressource en ligne; régions géographiques; soc2014; théories féministes; violences; états-unis